Shifting the lines of the British travel writing tradition: Marlow's vertical travel in Lord Jim - Isabelle LORÉAL (E-REA)
The representation of space in Lord Jim was at odds with the expected nineteenth century exotic landscape, posing as a mere backdrop to the adventurer’s feats. Jim's thwarted linear progression also signalled a modern shift in narration placing more emphasis on space and simultaneity than on chronological progress. In travel writing, the concept of “vertical travel” has recently emerged. A slower type of voyage, concerned with the minute details of a particular place, deep diving into the layered strata of its history enables the traveler to discover it anew. I will argue that Marlow's experience in Patusan already corresponds to this type of downwards travel. While the opening of the Suez Canal heralded the end of the period when it was still possible to discover unchartered territories on the surface of the earth, its drilling deep into the ground also signaled that exploration would need to become excavation, uncovering of what is layered stratigraphically under the surface. Conrad's geopoetics recreated space anew in a world with no blank space left to discover and signalled the end of romantic traveling. The deep chasm in the Patusan hills calls for an exploration of the depths as the new frontier for the exotic.